(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
An outdoor experimental study was carried out to investigate and compare the performance of two commercially available photovoltaic modules (polycrystalline and amorphous silicon) under the effect of temperature change in Usen Community, Edo state for the months of April, 2023 through August, 2023. Maximum power, module efficiency, and fill factor were calculated for each module and comparison was presented. Results show that polycrystalline module perform better at high irradiance and showed poor performance in low irradiance conditions. Amorphous solar module show a performance in low light condition and having high fill factor (FF). Polycrystalline photovoltaic module was found to be more efficient, having module efficiency of 13.5 percent higher than that of amorphous module. As a result of better performance in low solar irradiance, amorphous solar module has shown daily average fill factor of 0.62 which was higher than polycrystalline module under study.